From Structure to Behavior in Basolateral Amygdala-Hippocampus Circuits - Yang, Ying; Wang, Jian-Zhi (Frontiers in Neural Circuits, 2017)
Emotion influences various cognitive processes, including learning and memory.The amygdala is specialized for input and processing of emotion, while the hippocampus is essential for declarative or episodic memory.During emotional reactions, these two brain regions interact to translate the emotion into particular outcomes.Here,we briefly introduce the anatomy and functions of amygdala and hippocampus, and then present behavioral, electrophysiological, optogenetic and biochemical evidence from recent studies to illustrate how amygdala and hippocampus work synergistically to form long-term memory.With recent technological advances, the causal investigations of specific neural circuit between amygdala and hippocampus will help us understand the brain mechanisms of emotion-regulated memories and improve clinical treatment of emotion-associated memory disorders in patients.